Preventative care in student-run free clinics: a narrative review on feasibility, ethics, and recommendations - Anhmai Vu; Andrea R. Hsu; Nicholas M. Baumel; Jordan Holthe; Jade Y. Ho; Sophia Y. Goldberg; Leonardo Garcia Cerecedo; Nada Abou-Haiba; Robyn Kuchler; Zoe Fanning; Victoria Heigh; Edward Trimble; et al. (BMC Medical Education)
Abstract Background Student-run free clinics are critical for medical education and medical care of underserved populations. This paper explores the feasibility of establishing ethical preventative health services at student-run free clinics such as the Rochester Education and Advocacy for Community Health (REACH) Clinic, affiliated with the Mayo Clinic Alix School of Medicine. Our analysis discusses the challenges and ethical considerations of providing preventative healthcare in student-run clinics. This paper also provides recommendations for implementing preventative care at REACH and other student-run clinics. Methods A literature search was conducted by an experienced librarian across four databases using keywords “student-run clinics” and “preventative healthcare.” Additionally, contributing authors identified and gathered data about community service organizations that provide preventative healthcare services to residents of Rochester, MN and surrounding areas. Results The literature search yielded 50 articles, 20 of which were included in the narrative review. Vaccinations and cancer screenings were the two preventative care initiatives most commonly undertaken by student-run clinics. The benefits of student-run clinic initiatives for both patients and students were an emerging theme. Clinics often achieved high vaccination and screening rates, and integration of preventative care topics into medical curricula was valued by students. However, the limitations of student-run clinics also emerged as a theme, particularly limitations to resources and comprehensive follow-up. 15 community health organizations in/around Rochester, MN were identified; of these, five provide preventative healthcare services. Conclusion Student-run clinics like REACH play a key role in delivering preventative care to underserved populations, bridging critical gaps in our healthcare system, and benefiting patients and students alike. However, the ethical principles of beneficence and non-maleficence should be considered when student-run clinics decide what services to offer. Preventative care has been successfully implemented at other student-run clinics but requires careful arrangement of adequate follow-up care, especially when it comes to cancer screening. Vaccinations are a low-cost, high-impact initiative that can be feasibly implemented at most student-run clinics.